Balanced progress: optimal protection in a survival context - Stallman, R. K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Introduction: In any drowning episode, there is usually some factor, some weak or missing skill, which triggers the emergency. At any given stage of aquatic skill development, the optimal level of protection is achieved when all essential elements are evenly developed. Elsewhere, the principles of such development have been described as a) equally proficient on front and back, b) equally proficient underwater and at the surface, c) possession of a well balanced and all around aquatic skill base. A common example of persons without balanced development are those who are moderately skilful on the front but very weak on the back (or vice versa). Methods: A conceptual model is presented on the premise that the weakest element in a person`s skill profile is most likely to trigger an emergency situation in the water, i.e. a potential drowning. The chain is only as strong as the weakest link. From a previous study, in depth interviews with drowning survivors have uncovered typical weaknesses in skill development. Results: When skill development is uneven, weak spots or holes are left in the foundation. Because foundational skills are weak or missing, the next row of bricks (skills) is weaker. Pressure grows as the wall gets higher. One missing brick leads to another. A fault line develops. Finally, the wall collapses. A weak or missing essential survival element has triggered a drowning episode. Conclusions: Water safety education must strive for balanced development of essential protective skills.